2017
DOI: 10.1021/acs.jafc.7b00068
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Assembled Nano-aggregates in Clear Green Tea Infusions from Camellia ptilophylla and Camellia sinensis

Abstract: Tea nano-aggregates spontaneously assembled in clear tea infusions are considered as the precursors of tea cream, although their molecular basis remains obscure. Here, we characterized nano-aggregates in green tea infusions from Camellia ptilophylla, a peculiar tea variety with 6.0% of theobromine, and Camellia sinensis as the control for comparative purpose. Numerous negatively charged spherical colloidal particles of 50-100 nm in diameter were primarily found in both green tea infusions. Catechins, proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…For instance, the proteoglycan–lipid NPs with an average diameter of 50–67 nm were generated during the heating processing of Freshwater Clams ( Corbicula fluminea Muller) soup ( 12 ). Numerous spherical NPs were found in green tea infusions ( 13 ). A large number of self-assembly micro/nanoparticles containing docosahexaenoic acid (DHA) and eicosatetraenoic acid (EPA) have been observed in bigeye tuna ( Thunnus obesus ) head soup ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the proteoglycan–lipid NPs with an average diameter of 50–67 nm were generated during the heating processing of Freshwater Clams ( Corbicula fluminea Muller) soup ( 12 ). Numerous spherical NPs were found in green tea infusions ( 13 ). A large number of self-assembly micro/nanoparticles containing docosahexaenoic acid (DHA) and eicosatetraenoic acid (EPA) have been observed in bigeye tuna ( Thunnus obesus ) head soup ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have reported on the precipitation of tea infusions, and although the majority of them are focused on analysis of the chemical constitution of the precipitate, a few study the effects of different tea cultivars, extraction methods (time, temperature, and pH) and storage conditions (temperature and duration) on the components and amount of precipitate. Generally, green tea infusion precipitate is a negatively charged spherical nanoaggregate with a D H distribution of 106 to 2305 nm and diameters of 50 to 100 nm. The aggregates have an average zeta-potential value of −14.7 ± 0.3 mV. The components of the green tea infusion that precipitate include catechins, caffeine, carbohydrates, proteins, amino acids (theanine, aspartic acid, and glutamic acid), and metal ions (Ca 2+ , K + , Mg 2+ , Mn 2+ , Na + , Zn 2+ , and Al 3+ ). Of those, polyphenols (29.86–78.66%), total saccharides (14.47–27.62%), and caffeine (2.35–10.43%) were found to be the dominant components in green tea cream. , In particular, catechins, which are the main components in tea polyphenols (TP), reached a percentage of 12.8–42.5%.…”
Section: Introductionmentioning
confidence: 99%
“…With the trend of cold brew (Liu et al, 2017 ; Song et al, 2021 ) on the rise, consumers generally use boiling water to brew green tea. The brewing temperature affects the concentration of the components, such as caffeine (Liu et al, 2017 ), in the tea infusion, as well as the aroma and taste of the tea infusion. When a green tea infusion is stood for certain days, the brewing temperature has no effect on its turbidity, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have confirmed that caffeine and ester catechins were the principal constituents of green tea cream (Xu & Yin, 2010 ). Amino acids also participated in the formation of tea cream (Lin et al, 2017 ; Xu & Yin, 2010 ), thus, the product of catechin contents and amino acid contents, as well as the product of the ester catechin contents and amino acid contents could be used to distinguish between different grades of the same kind of green tea.…”
Section: Resultsmentioning
confidence: 99%